(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Community-acquired pneumonia remains one of the most common infectious diseases affecting children and a major cause of antibiotic prescription in pediatric practice. The effectiveness and safety of antibacterial therapy largely depend on age-related factors such as pathogen distribution, immune system maturation, pharmacokinetic characteristics, and susceptibility to adverse drug reactions. Pharmacoepidemiology provides a valuable framework for evaluating real-world antibiotic use, resistance trends, and clinical outcomes across different pediatric age groups. This article presents a comprehensive analysis of age-specific antibacterial drug utilization in the treatment of pediatric community-acquired pneumonia, emphasizing rational selection, dosing considerations, and population-based evidence. By integrating epidemiological surveillance data with clinical observations, the study highlights strategies to optimize therapy, improve outcomes, and support antimicrobial stewardship in children. Pediatric community-acquired pneumonia continues to represent a major clinical and public health challenge due to its high incidence, variable clinical course, and frequent need for antibacterial therapy. Differences in age-related physiology, immune response, and exposure patterns significantly influence both disease manifestation and therapeutic response. From a pharmacoepidemiological viewpoint, analyzing population-level prescribing trends allows a deeper understanding of how antibacterial agents are selected and used across childhood. This section provides a comprehensive overview of how age stratification contributes to more effective, safer, and resistance-conscious antibacterial treatment strategies, emphasizing the importance of real-world data in guiding rational clinical decisions.